Body size regulation and insulin-like growth factor signaling. - Hyun, S. (Cellular and molecular life sciences. CMLS, 2013)
How animals achieve their specific body size is a fundamental, but still largely unresolved, biological question. Over the past decades, studies on the insect model system have provided some important insights into the process of body size determination and highlighted the importance of insulin/insulin-like growth factor signaling. Fat body, the Drosophila counterpart of liver and adipose tissue, senses nutrient availability and controls larval growth rate by modulating peripheral insulin signaling. Similarly, insulin-like growth factor I produced from liver and muscle promotes postnatal body growth in mammals. Organismal growth is tightly coupled with the process of sexual maturation wherein the sex steroid hormone attenuates body growth. This review summarizes some important findings from Drosophila and mammalian studies that shed light on the general mechanism of animal size determination.